Evaluation of Intravenously Delivered Allogeneic Mesenchymal Stem Cells for Treatment of Elbow Osteoarthritis in Dogs: A Pilot Study - Olsen, Anastasia; Johnson, Valerie; Webb, Tracy; Santangelo, Kelly S.; Dow, Steven; Duerr, Felix M. (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objectives The aim of this study was to evaluate the safety and collect pilot data measuring clinical effects of intravenously administered, adipose-derived, culture-expanded, allogeneic mesenchymal stem cells in dogs with elbow osteoarthritis.Materials and Methods Dogs (n = 13) with naturally occurring elbow osteoarthritis received three intravenous doses of allogeneic canine mesenchymal stem cells via an open-label clinical trial. Primary outcome measures collected over a 6-month study period included objective gait analysis, accelerometry, owner questionnaires and joint fluid analysis.Results No acute adverse events were observed following repeated intravenous treatment with allogeneic mesenchymal stem cells. A significant improvement in mean client-specific outcome measure (CSOM) activity score and CSOM behaviour score was observed when pre-treatment values were compared with post-treatment values (day >28). In contrast, mean peak vertical force significantly decreased from baseline to post-treatment (>day 28). Weekly activity counts did not show a significant difference between baseline to post-treatment time points. Synovial fluid biomarkers did not change during treatment, and labelled mesenchymal stem cells were rarely detected in synovial fluid samples collected after mesenchymal stem cell administration.Clinical Significance For dogs with naturally occurring elbow osteoarthritis, intravenous administration of mesenchymal stem cells was clinically well tolerated. While some subjective outcome measures showed significant improvements, objective outcome measures did not confirm similar changes. Further research is needed before intravenous mesenchymal stem cells can be recommended as a treatment for elbow osteoarthritis in dogs.
Keywords: cartilage degeneration; cell-based therapies; clinical lameness; degenerative joint disease; elbow osteoarthritis